Transtornos mentais comuns entre trabalhadores da zona urbana de Feira de Santana – BA - Farias, Mônica Dantas (2007)
The Common Mental Disorders (TMC) are one of the main causes of morbidity that affect a significant part of the population. Studies point at the importance of the socioeconomic conditions and the characteristics of labor as possible risk factors to the occurrence of mental disorders among workers. The changes that happened in the world of labor such as productive restructuring and flexible accumulation brought consequences to the production process and mainly for the workers. The labor conditions can affect the biopsychic health of the workers and can cause sickness. The goal of this paper was to describe the prevalence of Common Mental Disorders in workers of the urban zone in the county of Feira de Santana, Bahia, Brazil based on the socio-demographic characteristics and professional labor. A study of cross cutting was done including workers of the same age or superior to 15 years of age in paid activities with or without labor vinculum that live in the urban zone of the county. A residence sheet was used as well as a questionnaire containing questions about socio-demographic characteristics, professional work characteristics, psychosocial job aspects and mental health. To evaluate the psychosocial aspects of work, the Job Content Questionnaire (JCQ) was used and to measure the common mental disorders a Self-Reporting Questionnaire (SRQ-20) was used. A uni-and multi varied analysis was carried out (analysis of multiple logistic regression). 1,311 workers were studied. The global prevalence of TMC was of 25.2 %. Findings obtained in the logistic regression revealed a statistically significant association among the TMC and socio-demographic variables like sex, schooling, income, life style, leisure and high job demand characteristics. The results of this study point at the attention towards the organization of work and the mental health of the workers and suggest serious thought as to the possibilities of public engagements that lead to the improvement of life conditions, labor and mental health of the workers.